School Service Management Policy in Improving Parents’ Understanding of Program Indonesia Pintar (PIP) Fund Utilization - Muhammad Ghaffar Rasyad (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study examines school service management policies in improving parents’ understanding regarding the utilization of Program Indonesia Pintar (PIP) funds at MTsN 1 Kota Cirebon. The research aims to analyze the implementation of school management services, identify parents’ understanding of educational assistance utilization, and explore supporting and inhibiting factors affecting policy implementation. This study employed a qualitative case study approach. Data were collected through in-depth interviews, participatory observation, and documentation involving the principal, teachers, administrative staff, and parents of PIP recipients. Data validity was ensured through source, technique, and time triangulation, while analysis followed the interactive model of Miles, Huberman, and Saldaña involving data reduction, data display, and conclusion drawing. The findings reveal that school management services were implemented through socialization programs, administrative assistance, transparent communication, and monitoring of educational fund utilization. These strategies significantly contributed to improving parents’ understanding regarding the proper use of PIP funds for educational purposes. However, parents’ understanding remained influenced by educational background, economic conditions, access to information, and educational awareness. The study further indicates that integrating Islamic values such as amanah, honesty, responsibility, and justice strengthened educational service effectiveness and community trust. Therefore, effective school service management is essential for ensuring the successful implementation of educational assistance policies and strengthening parental participation in supporting children’s education